2016
DOI: 10.1007/s11999-016-4848-6
|View full text |Cite
|
Sign up to set email alerts
|

Among Musculoskeletal Surgeons, Job Dissatisfaction Is Associated With Burnout

Abstract: Background Burnout is common in professions such as medicine in which employees have frequent and often stressful interpersonal interactions where empathy and emotional control are important. Burnout can lead to decreased effectiveness at work, negative health outcomes, and less job satisfaction. A relationship between burnout and job satisfaction is established for several types of physicians but is less studied among surgeons who treat musculoskeletal conditions. Questions/purposes 123Clin Orthop Relat Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
(45 reference statements)
1
22
0
1
Order By: Relevance
“…In addition, respondents who endorsed feeling supported outside of residency, who believed their opinion was valued within the department, and who self-identified as mentors to junior trainees and students all scored significantly higher in empathy than those who did not. This finding corroborates previous work showing the benefits of establishing social support systems and the importance of promoting engagement in and deriving meaning from work 29 , 34 , 35 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, respondents who endorsed feeling supported outside of residency, who believed their opinion was valued within the department, and who self-identified as mentors to junior trainees and students all scored significantly higher in empathy than those who did not. This finding corroborates previous work showing the benefits of establishing social support systems and the importance of promoting engagement in and deriving meaning from work 29 , 34 , 35 .…”
Section: Discussionsupporting
confidence: 91%
“…In the past years, job satisfaction and burnout rates among physicians have gained attention in recent literature. [18][19][20] Prior research showed that 80% of US neurosurgeons reported to be at least somewhat satisfied with their career and 52% believed their professional lives would worsen in the future. According to their survey, 56.7% of these surgeons had a burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Workload and stress levels are higher than in other medical specialties [3, 7]. The high stress levels can contribute to burnout [9], which has been shown to be associated with lower satisfaction with various aspects of the work situation in a variety of studies [4, 1012]. Surgeons do indeed report lower job satisfaction than other physicians [13].…”
Section: Introductionmentioning
confidence: 99%